Process of l1 acquisition: linguistic theory in application - M. Shah, Parilah; Yusof, Aminuddin; Abdul Hamid, Zaidatul Akmal; Abdul Ghafar, Salehan; Hashim, Harwati; Abdullah, Amizura; M Sabri, Munira (Villanova University, 2010)
Children acquire knowledge of the first language (L1) without formal instruction in a variety of different circumstances. This paper analyzes how linguistic theory models first language acquisition in a way that is consistent with the fact that formal instruction is not available and that the circumstances for different children vary unpredictably, though the outcome is largely the same. Each part of the Universal Grammar Model is discussed with relevant examples.